Clinico-pathological features of tuberculosis due to Mycobacterium tuberculosis Uganda genotype in patients with tuberculous lymphadenitis: a cross sectional study - Wamala, Dan; Asiimwe, Benon; Mboowa, Gerald; Kallenius, Gunilla (BMC clinical pathology, 2014)
Tuberculous lymphadenitis is next to pulmonary tuberculosis as the most common cause of tuberculosis. Uganda genotype, one of the sub-lineages of Mycobacterium tuberculosis, is the most prevalent cause of pulmonary tuberculosis in Uganda. We here investigate the clinicopathological characteristics of patients with tuberculous lymphadenitis infected with M. tuberculosis Uganda genotype compared with those infected with M. tuberculosis non-Uganda genotype strains. Between 2010 and 2012, we enrolled 121 patients (mean age 28.5 yrs, male 48%; female 52%) with tuberculous lymphadenitis, and categorized them by their M. tuberculosis genotypes. The clinical features and lymph node cytopathological parameters were compared between patients in the Uganda and non-Uganda categories using a crude and multivariable logistic regression model with adjustment for confounding factors. Of the 121participants, 56 (46%) were infected with strains of Uganda genotype. Patients infected with this genotype had significantly lower frequency of abdominal lymphadenopathy (odds ratio 0.4, p = 0.046) after adjusting for sex, age and HIV. Abdominal lymphadenopathy was also significantly associated with abnormal chest X-ray (p = 0.027). Tuberculous lymphadenitis patients infected with M. tuberculosis Uganda genotype were significantly less prone to have abdominal lymphadenopathy indicating potential reduced ability to disseminate and supporting the concept that differences in M. tuberculosis genotype may have clinical implications.